The body, the architectural space and the city: performative experiences in Centro Cultural São Paulo (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article is based on performative experiences of Corpo e Paisagem, an artistic project held at Centro Cultural São Paulo (CCSP), in order to reflect on the relationships drawn between the body, the architectural space and the city. Starting with the historical context of the construction of CCSP and its architectural project, the text seeks to understand how the sensorial experiences of Corpo e Paisagem provided a sensitive reading of CCSP spaces, in order to perceive it not only in its evidences, but also in its implicit meanings. By accessing a kind of unconscious of the architecture, the contextual creations resulting from the project designed possibilities for action and occupation of spaces that do not reproduce patriarchal, colonialist and capitalist values present in CCSP architectural forms and in their rules of use.
Keywords: Body; Contextual; Dance; Architectura; City